Effect of feeding crushed and entire dried Prosopis juliflora pods on feed intake, growth and reproductive performance of arid goats - SIROHI, A S; MATHUR, B K; MISRA, A K; TEWARI, J C (The Indian Journal of Animal Sciences, 2017)
The present study was initiated with the objective to assess the feeding strategy comprising Prosopis juliflora pods (PJP) in two forms as alternative feed resource for sustainable goat production for dry season in arid areas. Eighteen growing goats (Marwari and Sirohi breed) were distributed into three groups. The roughage offered was similar to all the animals, however, concentrate mixture was standard for the goats of control group (PJP0), whereas, 50 percent ground PJP in PJPG group and 50 percent as such (entire/non-grinded) dried PJP in PJPE group were included by replacing the standard concentrate mixture. The observations on the animals were recorded for a period of seven months. Fifty percent replacement of concentrate mixture from similar to that of the standard concentrate mixture of PJP0 with crushed and entire PJP made diets economical by ₹ 471.50 and 521.50/quintal basis in PJPG and PJPE, respectively. Daily dry matter intake (DMI)/100 kg body weight was 4.53±0.19, 4.68±0.11 and 4.79± 0.17 kg in PJP0, PJPG and PJPE, respectively. The average body weight gain and body condition score of the animals did not differ significantly between the groups. Five goats from all the groups were bred, which became pregnant and delivered kids normally. The results revealed that the feeding of concentrate mixtures containing either 50% ground or entire PJP to the arid goats did not adversely affect growth performance, reproduction and cud chewing. Moreover, the adopted feeding strategy made Prosopis juliflora incorporated concentrate diets more economical than the commercial one.